Technopreneurship in Small Businesses - Hanhan Maulana; E S Soegoto; R Syahputra (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2021)
The purpose of this study is to show reports that revealed small businesses in Indonesia have many concerns about survival, competitiveness, and efficiency due to related issues such as finance, lack of information and knowledge, capabilities and capacity. This research is based on problems related to IT implementation in Indonesia. It determines the problems associated with implementation and identifies factors for successful IT implementation in Indonesia. The descriptive qualitative method with literature review was carried out to obtain data that has been changed in the form of book notes, newspapers, agendas, inscriptions, minutes of meetings, and magazines. This study intends to be a reference in the development of small businesses in Indonesia who are very concerned about the development of technology that can improve small businesses to utilize social media as promotion.